The Relationship between Perceptions of Insecurity, Social Capital and Subjective well-being: Empirical Evidences from Conflicted Rural Colombia (2010)
Subjective Wellbeing -SWB-, the evaluation people do of their lives, has been proposed as a measure to track the development of communities instead of economic growth. As part of a more general research question in which we tested the impact of subjective insecurity on the choice of hybrid organizational modes, we hypothesized that subjective insecurity does negatively correlate with SWB and that subjective and objective insecurities are not significantly correlated. Subjective insecurity consisted of three items: perceptions of personal, political and economic insecurity. We proposed that insecurity and SWB are mediated by the level of social capital found in the region. Social capital was defined as interpersonal trust as well as the frequency of participation of producers in voluntary associations. We used a multiple and multilevel regression models to test the hypotheses. Based on a survey of 742 rural producers in five conflicted areas we tested and found that the perceptions of insecurity do correlate significantly (negatively) with levels of subjective wellbeing. We also found a significant contribution of social capital with levels of SWB. Significant correlations between demographic variables and SWB were replicated at rural areas. These results have important implications for public policy and future research.